Design of a Microstrip Patch Antenna Array for Airborne SAR Applications - Vetharatnam, G.; Chung, B. K.; Chuah, H. T. (2005)
A microstrip patch antenna array has been developed for a C-band airborne Synthetic Aperture Radar. The antenna operates at 6 GHz with a bandwidth of 168 MHz (SWR < 1.5). It is a rectangular patch fed by a probe from a feed network placed behind the ground plane. A cost effective substrate with low dielectric constant and moderate loss is used for the patch and feed network. The antenna has an optimally shaped beam pattern (with a beamwidth of 24 degrees) in the E-plane with the sidelobe suppressed by 15 dB. In the H-plane, a narrow beamwidth of 3 degrees is designed with the sidelobes suppressed by 30 dB. The antenna achieved a gain of 21.2 dBi. A practical method to compensate for the losses in the feed distribution network is introduced.